Análisis de la microfacturación en la Isla Decepción, Antártida Occidental - González Casado, José Manuel; López Martínez, Jerónimo; Giner Robles, Jorge Luis; Durán Valsero, Juan José; Gumiel Garrido, P. (Sociedad Geológica de España, 1999)
The micro fracture patterns in Deception Island, an active shield volcano located in the Bransfield Strait, Antarctic Peninsula region, are studied here for the first time. 143 faults have been measured in five sites along the island, three main trends NE-SW, E-W and NW-SE have been established. The average trend of all the measured faults is N46°E. The faults are several meters long and produce small displacement of the pyroclastic layers (up to some tens of centimetres). AII of them have a dip higher than 60°, showing in general a normal sense of movement. This orientation, subparallel to the Bransfield Basin axis, seems to be related to the caldera formation as well as with the subsequent tectonic deformation. These faults are related to a NW-SE extension, compatible with the tectonic setting of this area. The NW-SE faults show directional movement, then they represent, probably, transfer faults of the former group. A small set of normal faults trending E-W has also been measured. Comisión Interministerial de Ciencia y Tecnología (España) Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub